Cellular Uptake of the ATSM−Cu(II) Complex under Hypoxic Conditions. Issue 4 (28th April 2021) - Walke, Gulshan R.; Meron, Shelly; Shenberger, Yulia; Gevorkyan‐Airapetov, Lada; Ruthstein, Sharon
Abstract: The Cu(II)‐diacetyl‐bis (N4‐methylthiosemicarbazone) complex (ATSM−Cu(II)) has been suggested as a promising positron emission tomography (PET) agent for hypoxia imaging. Several in‐vivo studies have shown its potential to detect hypoxic tumors. However, its uptake mechanism and its specificity to various cancer cell lines have been less studied. Herein, we tested ATSM−Cu(II) toxicity, uptake, and reduction, using four different cell types: (1) mouse breast cancer cells (DA‐3), (2) human embryonic kidney cells (HEK‐293), (3) breast cancer cells (MCF‐7), and (4) cervical cancer cells (Hela) under normoxic and hypoxic conditions. We showed that ATSM−Cu(II) is toxic to breast cancer cells under normoxic and hypoxic conditions; however, it is not toxic to normal HEK‐293 non‐cancer cells. We showed that the Cu(I) content in breast cancer cell after treatment with ATSM−Cu(II) under hypoxic conditions is higher than in normal cells, despite that the uptake of ATSM−Cu(II) is a bit higher in normal cells than in breast cancer cells. This study suggests that the redox potential of ATSM−Cu(II) is higher in breast cancer cells than in normal cells; thus, its toxicity to cancer cells is increased. Abstract : A copper‐based hypoxic PET imaging biomarker, is found to be toxic to breast cancer cells under normoxic and hypoxic conditions. However, the complex is non‐toxic to normal HEK‐293 non‐cancer cells. It is suggests that the redox potential of the investigated copper complex is higher in breast cancer cells than in normal cells.